Inter-ethnic consent in the cultural and сivilizational context - Alikenova, K. N. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2016)
The given article shows the political and civilizational existence of ethnic groups in Kazakhstan on the basis of the analysis of the characteristics of their cultural development. Consisting of various ethnic groups of mankind requires a logical concept combining the total measurement. Generically human civilization, universal achievements, the formation of a common destiny revealed on the basis of fundamental cultural values. It includesthe individuality in a society, secular and religious humanism, freedom of conscience, aesthetic beauty, some economic value, ecological concepts, etc. Ethnic identification shouldnot be remainend just as a slogan. Ethnos itself with the development must be modernized around the personality“ me” Various historical traditions, cultural processes interacting syncretically join together and make an impact on the uniqueness of the Kazakh mentality and forms a unique singularity of national culture.